Learning by Camping - Hochkeppel, Nicola (Germany, 2004)
Verzio FF submission Tax consultant Wagner, the head of a family leads his wife and seven children through endless summer pilgrimages by camper. This German vacation idyll chronicles the history of a family, a country, and a medium – Super 8 filmmaking.